A practical guide to early repolarization. (January 2015) - Adler, Arnon; Gollob, Michael H.
<x xml:space="preserve">Abstract</x> Purpose of review Early repolarization has been associated in the past decade with idiopathic ventricular fibrillation and arrhythmic death. The purpose of this review is to clarify recent changes in the definition of early repolarization and provide a practical approach to patients with this electrocardiographic sign. Recent findings Recent population studies have associated early repolarization with arrhythmic death. Challenges remain, however, in interpreting the risk of the early repolarization electrocardiographic pattern, as it is a common finding in the general population with a prevalence of 3–13%. Early repolarization characteristics associated with an especially high risk include high-amplitude J-point elevation, horizontal/descending ST segment, and inferior lead location. In view of the association of early repolarization with sudden death, a syndrome termed 'early repolarization syndrome' (ERS) has been accepted as the latest 'channelopathy' in patients with cardiac arrest, pronounced early repolarization pattern, and an otherwise structurally normal heart. The physiological basis of early repolarization is thought to involve an electrical transmural gradient produced by the transient outward current. Recent genetic studies have associated mutations in genes contributing to this current and other ion channels with ERS, although definitive genetic data do not yet exist to confirm pathogenicity. Summary ERS patients are rare and have a high risk of recurrent cardiac events. ICD implantation and possibly quinidine are the recommended treatments in this group. Opposingly, asymptomatic individuals with early repolarization are very common and, as a group, have a good prognosis. Sudden death preventive measures in these asymptomatic patients are limited to rare and unique cases.